Professional management of housekeeping operations - Jones, Thomas J. A. (Hoboken, New Jersey : John Wiley & Son, Inc., 2008)
"Professional Management of Housekeeping Operations is the essential practical introduction to the field, a complete course ranging from key principles of management to budgeting, from staff scheduling to cleaning."
Part 1. The housekeeping profession and the principles of management -- Part 2. Planning, organizing, and staffing the new organization -- Part 3. Directing and controlling ongoing housekeeping operations -- Part 4. Special topics: swimming pool operations and management, housekeeping in other venues, safeguarding of assets, in-house laundries, and the full circle of management.
Includes index.
Keywords: HOTEL HOUSEKEEPING